Hannibal and the paradox of disgust. Issue 5 (3rd September 2019) - García, Alberto N.
ABSTRACT: Hannibal (NBC 2013–15) is a bloody and violent television series that also displays an embellished and self-consciously expressive visual style. This article explores the disparity between aesthetic pleasure and repugnance, an issue that scholars working in aesthetic theory have dubbed the 'paradox of disgust'. It begins by focusing on the specific qualities of disgust among the so-called 'negative' emotions in art, and develops this analysis through a close reading of significant scenes in Hannibal . Drawing on Strohl's 'hedonic ambivalence', the article argues that Hannibal intensifies its aesthetic value precisely by visually boosting the paradox of disgust, maximizing both aversion and pleasure simultaneously. However, the article also shows that Hannibal attempts to circumvent the paradox of disgust by prompting an 'aestheticist turn', embodied in the experience of protagonist Will Graham.